Health economic evaluation of different colorectal cancer screening strategies in Hubei province: a Markov simulation analysis based on local cancer registration and domestic study data - Jie JI; Yuying WANG; Duan ZHUO; Yuhan LIU; Jiaxi PENG; Ruijingfang JIANG; Hao WU; Song LIU; Lijian ZHAO; Jian WANG; Bing MAO; Shida ZHU; et al. (Zhongguo gonggong weisheng)
ObjectiveTo construct a Markov decision model for colorectal cancer screening, evaluate the long-term cost-effectiveness of different screening strategies, determine the optimal screening strategy, and provide a theoretical reference for improving colorectal cancer screening programs. MethodsA Markov decision model was constructed to simulate 25 screening strategies, including no screening, with screening start ages of 40, 45, and 50 years, end ages of 59, 64, 69, and 74 years, and screening intervals of 1 and 2 years. Data on the probabilities, screening costs, and medical costs required for the colorectal cancer natural history model were extracted from the Hubei Provincial Cancer Registration (2020)/Mortality Surveillance (2013 – 2017) dataset and the literature review and entered into the model. With a cycle length of 1 year, the health economic impact of different colorectal cancer screening strategies was predicted over multiple cycles. ResultsThe cost-effectiveness analysis at the individual level showed that the screening strategy with the lowest cost was 50-74-1 (annual primary screening with immunochemical fecal occult blood testing [iFOBT] and then required colonoscopy from 50 to 74 years of age), which cost 483 100 Chinese yuan (CNY) in social costs, gained 17.82 life-years (LY) and 16.76 quality-adjusted life-years (QALY), with a cost-effectiveness ratio (CER) of 27 100 CNY/LY and 28 800 CNY/QALY, using LY and QALY as outcome measures, respectively. The payback analysis showed that the 45-74-1 strategy (annual primary screening with iFOBT and then required colonoscopy from age 50 to 74 years) had the best cost-effectiveness ratio, consuming 515 200 CNY, gaining 19.49 LY and 18.37 QALY, with a CER of 26 400 yuan/LY and an incremental cost-effectiveness ratio (ICER) of 19 200 yuan/LY when using LY as the outcome measure, and a CER of 28 000 CNY/QALY and an ICER of 19 900 CNY/QALY when using QALY as the outcome measure. The strategy with the highest effect was 40-74-1 (annual screening from age 40 to 74), which cost 551 700 CNY in social costs and gained 20.97 LY and 19.78 QALYs, with a CER of 26 300 CNY/LY and an ICER of 24 700 CNY/LY using LY as the outcome measure, and a CER of 27 900 CNY/QALY and an ICER of 26 000 CNY/QALY using QALY as the outcome measure. The current colorectal cancer screening strategy in Wuhan, Hubei province, is 45-59-2 (biennial screening from age 45 to 59), which costs CNY 1 035 100 in social costs and gains 18.97 LY (16.8 QALY). The 45-74-1 strategy is more economical than the current strategy in Wuhan, saving 519 900 CNY and gaining an additional 0.52 LY (1.57 QALY). Considering the principle of maximum effect, the 40-74-1 screening strategy can save 483 400 CNY and gain an additional 2.00 LY (2.98 QALY) compared with the current colorectal cancer screening strategy in Wuhan. ConclusionUnder ideal economic conditions, the strategy (40-74-1) with the greatest effect can be prioritized; under limited economic resources, the screening strategy (45-74-1) with the best cost-effectiveness ratio can be prioritized.